A gene and protein expression study on four porcine genes related to intramuscular fat deposition. (November 2016) - Zappaterra, Martina; Deserti, Marzia; Mazza, Roberta; Braglia, Silvia; Zambonelli, Paolo; Davoli, Roberta
Abstract: Intramuscular fat (IMF) content has a prominent role in meat quality, affecting sensory attributes such as flavour and texture. In the present research, we studied in samples of porcine Semimembranosus muscle four genes related to lipid metabolism and whose gene expressions have been associated to IMF deposition: FASN, SCD, LIPE and LPL . We analysed both mRNA and protein expressions in two groups of Italian Large White pigs divergent for Semimembranosus IMF deposition, with the aim of comparing the levels of four genes and enzymes between the two groups and identifying possible coexpression links. The obtained results suggest a prominent role of LIPE enzyme in IMF hydrolysis, as the samples with low IMF deposition show a significantly higher amount of this lipase. Finally, a poorly known correlation was found between LIPE and FASN enzymes only in female individuals. These results provide new information for the understanding of IMF deposition. Highlights: Intramuscular fat content plays an important role in pig meat quality. We studied FASN, LIPE, LPL and SCD in two pig groups divergent for IMF deposition. LIPE enzyme was more expressed in samples showing lower intramuscular fat content. LIPE and FASN enzymes are linked by an unknown sex-dependent coexpression pathway.